2012
DOI: 10.1016/j.matdes.2012.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water absorption on the mechanical properties of nano-filler reinforced epoxy nanocomposites

Abstract: a b s t r a c tThis study aimed to investigate the effect of water absorption on the mechanical properties of nano-filler reinforced epoxy nanocomposites as well as to study the influence of different types of nano-fillers such as nano-clay platelets, halloysite nanotubes (HNTs) and nano-silicon carbide (n-SiC) particles on the water absorption behaviour of epoxy based nanocomposites. Results indicated that the addition of nano-fillers into epoxy matrix was found to decrease both water uptake and diffusivity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
150
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(178 citation statements)
references
References 36 publications
15
150
0
Order By: Relevance
“…This measurement frequently used roughness amplitude parameter as it measures the roughness of samples surfaces [36]. The minimum increase of coarseness is an evident of crack deflection mechanism, which increase absorbed energy of fracture by increasing the crack length during deformation [10]. Microscale surface roughness likely produces enhanced mechanical interlocking with the polymer chains and better adhesion [50].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This measurement frequently used roughness amplitude parameter as it measures the roughness of samples surfaces [36]. The minimum increase of coarseness is an evident of crack deflection mechanism, which increase absorbed energy of fracture by increasing the crack length during deformation [10]. Microscale surface roughness likely produces enhanced mechanical interlocking with the polymer chains and better adhesion [50].…”
Section: Resultsmentioning
confidence: 99%
“…The degree of liquid absorption and polymer degradation can be reduced by using nano-fillers such as nanoclay. Alamri and Low in their research reported that halloysite nanoclays were able to reduce water absorption and increase the mechanical properties of epoxy through uniform dispersion [10] [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compression properties of GRE pipe filled with geopolymer were observed from the optimum loading of geopolymer filler at 30 wt% of the geopolymer filler loading for 4 M white clay geopolymer filler, which contributed to enhancements in the interfacial bonding between the filler and the matrix, thus increasing the surface area of matrix and filler interaction. This leads to a good stress transfer from the matrix to the micro-filler, thus resulting in improved compressive strength [14]. Compressive modulus of stiffness materials in the static bending condition is tabulated in table 3.…”
Section: Compressionmentioning
confidence: 99%
“…Alamri and Low studied the effect of water on the mechanical properties of halloysite nanotubes-reinforced epoxy. They observed that the incorporation of halloysite nanotubes was able to reduce water absorption and improve mechanical properties of the nanocomposites after water immersion [19].…”
Section: Introductionmentioning
confidence: 99%